Women's public lives and sovereign arrangements in Karachi's inner city. Issue 3 (4th March 2018) - Viqar, Sarwat
Abstract: Women's public lives in Pakistan are often presented through tropes of oppression and restricted mobility. While women do struggle with all kinds of limitations that curtail their movement in the public sphere, they also negotiate their way and find their place in the public realm through various means that remain understudied in this context. In this article I track women's movements in public space in the historic quarters of Karachi, Pakistan's largest and most populous city. What emerges in the study is that a key aspect of women's movement through their neighbourhood is their membership in or attachment to various sovereign arrangements – political and religious, formal and informal – that seek to rule and govern the space of the quarter. These arrangements include political parties and groups, religious organizations and the shrines of Sufi saints. Ultimately I argue that women's public lives are driven not so much by the assertion of an individualized citizenship as by an attachment to and association with collective arrangements that allow a participation in the making of political and religious imaginaries.